Influência dos parâmetros de soldagem de revestimento com aço inox 308L - Cardim, Pedro Peres (2018)
Stainless steel cladding has been widely used in industry since it allows the creation of anticorrosive surfaces on low cost materials such as carbon steel and low alloy steels. However, to ensure the quality of the coating, the welding processes must be properly regulated, therefore obtaining the desired weld bead geometry and presenting good productivity. In this paper, a comparative study of the influence of the welding speed and the distance between the electrode and the part on the morphology of the weld beads was analyzed. The variables of response were width, reinforcement and penetration of the beads. The MIG process, frequently used in coating welding and easily automated, was used for the deposition of ABNT 308L stainless steel on ABNT 1020 steel samples. The bigger width and reinforcement were obtained with 250 mm/min welding speed and with a 20 mm distance between the electrode and the part. The smaller penetration was obtained with 300 mm/min welding speed and with a 25 mm distance between the electrode and the part.